The Dynamics of Public Opinion Representation in Government Social Media Comment Columns - Mazidatus Saadah; Mursalim; A. Rivai Beta (Wardah, 2026)
This study examines the phenomenon of comment manipulation on the official Instagram account of the East Kalimantan Provincial Government (@pemprov_kaltim) by highlighting indications of the use of inauthentic accounts that have the potential to shape perceptions of public support digitally. The study aims to identify the characteristics of these accounts and analyze how inorganic comments shape public perception. The study uses a qualitative approach with content analysis methods, through data collection in the form of screenshots, profile searches, metadata recording, and direct observation of specific posts. The results show that the fake accounts have consistent patterns such as minimal activity, unclear identities, uniform comments, and close posting times. This pattern creates a simulation of support that is not rooted in actual public opinion, thus creating hyperreality according to Baudrillard's concept. This comment manipulation also functions as noise that disrupts public communication, damages deliberative space, and prevents institutions from obtaining fully authentic feedback. From the perspective of Islamic communication ethics, this practice is considered a tadlis act because it falsifies the impression and violates the principles of honesty and justice as emphasized in QS Al-Māidah verse 8. The findings of this study confirm that comment manipulation has the potential to weaken public trust and create a digital reality that does not reflect the actual social conditions.